The Seven Chakra Sisters : Make Friends with the Inner Allies Who Keep You Healthy, Laughing, Loving, and Wise - Rosenthal, Linda Linker (United State America Hampton Roads Publishing, 2013)
Every spiritual seeker knows that there are seven main chakras-also described as energy centers or wheels of light. Blocked energy in the chakras can often lead to physical illness as well as spiritual malaise. The trick is how to balance these systems in our lives, and in The Seven Chakra Sisters, spiritual psychotherapist and healer Linda Rosenthal shows us exactly that. Rosenthal takes readers on a metaphysical, metaphorical romp into the world of the 7 chakras. She offers a delightful teaching fable about the unique personalities of the 7 Chakras to help us understand the important role they play in our health and well being. Rosenthal paints a wonderfully vivid portrait of these 7 chakra 'sisters' that live in all of us to teach the principles of energy healing and show readers how to bring the chakras into optimal alignment: * Aneeda, the Needy One, the root chakra (red). * Ivanna, the Wanting One, the sacral chakra (orange). * Ahafta, the One Who Has to, the solar plexus chakra (yellow). * Ahluvya, the Loving One, the heart chakra (green). * Singya, the Expressive One, the throat chakra (blue). * Useeme, the All-Seeing One, the third eye chakra (indigo). * Iamone, the One of Oneness, the crown chakra (violet). Through her light-hearted and funny exploration of the personalities and relationships of these chakra siblings, Rosenthal seriously shows readers how to achieve optimal physical and emotional health.
Including Glossary
Keywords: Chakras -- Conduct of life -- Women--Health and hygiene